2018
DOI: 10.1001/jamaoto.2018.0652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pure-Tone Audiologic Thresholds for Pediatric Cochlear Implant Candidacy

Abstract: IMPORTANCEAlthough current guidelines recommend cochlear implantation only for children with profound hearing impairment (HI) (>90 decibel [dB] hearing level [HL]), studies show that children with severe hearing impairment (>70-90 dB HL) could also benefit from cochlear implantation. OBJECTIVE To perform a systematic review to identify audiologic thresholds (in dB HL) that could serve as an audiologic candidacy criterion for pediatric cochlear implantation using 4 domains of speech and language development as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We suggest that more consistent approaches to data collection, for example, by developing core outcome sets or establishing other forms of international consensus on choice of outcomes, would aid future evidence syntheses in addition to greater consistency in how study populations are defined by inclusion and exclusion criteria. Scoping reviews such as this are complimentary to systematic reviews such as that of de Kleijn et al (2018) in part because they can catalogue a wider range of outcomes, and study designs, and in doing so identify gaps for further research to address, and opportunities for formal meta-analyses to be conducted where there is evidence of comparable outcome data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that more consistent approaches to data collection, for example, by developing core outcome sets or establishing other forms of international consensus on choice of outcomes, would aid future evidence syntheses in addition to greater consistency in how study populations are defined by inclusion and exclusion criteria. Scoping reviews such as this are complimentary to systematic reviews such as that of de Kleijn et al (2018) in part because they can catalogue a wider range of outcomes, and study designs, and in doing so identify gaps for further research to address, and opportunities for formal meta-analyses to be conducted where there is evidence of comparable outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to ensure that our review complemented rather than duplicated (Bond et al 2009a). We therefore searched for studies published from July 2007 to the present, immediately following the search by Bond et al (2009a), but overlapping the period considered by de Kleijn et al (2018) due to the more restricted range of outcomes they considered. Only peer-reviewed records were included.…”
Section: Methodsmentioning
confidence: 99%
“…While the expansion of the indication to recognize the benefits of adequate binaural hearing, the literature suggests that children with greater degrees of word understanding in the poorer hearing ear may similarly benefit from implantation. 52,[55][56][57] Further, children under the age of 5 have also been successfully implanted. Cushing et al suggest that every effort must be made to limit the period of auditory deprivation in CI candidate ear, encouraging CI as early as possible before the age of 4 years in the case of congenital deafness.…”
Section: Pediatric Cochlear Implantationmentioning
confidence: 99%
“…The review identified PTA >80 dB HL as a criterion for cochlear implantation. 9 These guidelines may still be overly restrictive. Carlson et al reported that 51 pediatric implant recipients with greater residual hearing than specified by current indications demonstrated a mean postimplant open-set speech recognition score of 85% in the cochlear implantation–only condition, which represented a 63–percentage point improvement over the preoperative aided score.…”
Section: Impact Of Early Cochlear Implantation On Speech and Language...mentioning
confidence: 99%